2006
DOI: 10.1007/s10578-006-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Awareness of Anxiety Symptoms in Children

Abstract: The present study aimed to determine which anxiety symptoms in children are associated with teacher awareness and whether teacher awareness differs according to student age and gender. The Multidimensional Anxiety Scale for Children (MASC) was completed by 453 second through fifth grade students and teachers nominated the three most anxious students in their classrooms. A multivariate analysis of variance was conducted with MASC scale scores as the dependent variables. Children identified by teachers as anxiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 22 publications
(59 reference statements)
4
28
1
3
Order By: Relevance
“…The issues associated with mental health in rural areas were particularly concerning, especially School Mental Health (2011) 3:222-235 231 considering the lack of mental health resources and research addressing the mental health of adolescents from rural areas in South Australia (Judd, 2001;Papandrea, Winefield, & Livingstone, 2010). Similarly to comparable research that has been inconsistent regarding the effect of student-and teacher-related variables, such as age, gender, and concern for academic progress, and teacher referral behavior (Jackson & King, 2004;Lane et al, 2004;Layne et al, 2006;Pearcy et al, 1993;Severson et al, 2007), the results of the present study concerning teacher-related variables, e.g., the number of years spent teaching; gender; or age were not significantly associated with teacher referral-related attitudes and behaviors. This suggests that further study investigating this phenomenon is required to establish any possible relationships.…”
Section: ''Other'' Important Issuesmentioning
confidence: 89%
See 1 more Smart Citation
“…The issues associated with mental health in rural areas were particularly concerning, especially School Mental Health (2011) 3:222-235 231 considering the lack of mental health resources and research addressing the mental health of adolescents from rural areas in South Australia (Judd, 2001;Papandrea, Winefield, & Livingstone, 2010). Similarly to comparable research that has been inconsistent regarding the effect of student-and teacher-related variables, such as age, gender, and concern for academic progress, and teacher referral behavior (Jackson & King, 2004;Lane et al, 2004;Layne et al, 2006;Pearcy et al, 1993;Severson et al, 2007), the results of the present study concerning teacher-related variables, e.g., the number of years spent teaching; gender; or age were not significantly associated with teacher referral-related attitudes and behaviors. This suggests that further study investigating this phenomenon is required to establish any possible relationships.…”
Section: ''Other'' Important Issuesmentioning
confidence: 89%
“…For instance, the most commonly reported biases include students' age and gender, and the differing behavioral and performance expectations that exist among teachers (Jackson & King, 2004;Lane, Givner, & Pierson, 2004;Severson et al, 2007). Conversely, Pearcy, Clopton, and Pope (1993) and Layne, Bernstein, and March (2006) found that teacher ratings of need for referral did not differ for boys and girls, and there was no gender effect on the teachers' reported referral experience.…”
Section: Service Use For Externalizing Problems Versus Internalizing mentioning
confidence: 99%
“…Thus far, research on the ability of school personnel to recognize social anxiety in youth is inconclusive and has mostly focused on teachers. One study showed that teachers’ ratings were concordant with elementary-aged students’ self-reported social anxiety (Layne et al, 2006), while another study failed to demonstrate teachers’ ability to identify social anxiety in their students (Weeks et al, 2009). Further research is necessary to clarify teachers’ competence in identifying anxiety and to shed light on the ability of more highly trained school personnel (e.g., guidance counselors, social workers, nurses, etc) to identify internalizing disorders and refer youth to appropriate services.…”
Section: Discussionmentioning
confidence: 99%
“…For additional information on the screening phase of the study please refer to Layne, Bernstein, and March (2006). Of the 208 students, 101 completed the additional screening (107 were not interested, ineligible, or unreachable), which included separate administrations of the ADIS to the child and parent by the same interviewer.…”
Section: Methodsmentioning
confidence: 99%